Identifying Market Challenges and Opportunities in Mixed Farming System Piloted Sites of Mid-hills Of Nepal: The Khotang Case - Neupane, Nilhari; Shakya, Shristi; Koirala, Sanju; Khadka, Manohara (International Institute of Tropical Agriculture, 2024)
This report aims to identify the market challenges and opportunities of agriculture commodities in Eastern Nepal with a specific focus on Halesi-Tuwachung Municipality in Khotang district, which is one of the piloting sites of Mixed Farming System (MFS) of CGIAR’s initiative. The report is structured into seven major sub-sections as follows. The introductory section is followed by a presentation of key features of the study area and methods and sources of data/information used in the report. The third section highlights the agriculture market related observations and findings in the study area including the current state of market participation of farming households in Nepal, with specific data on market engagement in different regions, including Khotang. Fourth section highlights the agriculture market related policies from the federal to local context. The fifth section identifies key market related challenges including socio-economic, policy, and bio-physical challenges that impede the transition of subsistence farmers towards market-oriented agriculture. The sixth section identifies potential opportunities for integrating MFS into the market. The seventh section portrays the enabling conditions that can facilitate the integration of mixed farming systems into the market including the recommendations for policymakers, development practitioners, and market players to promote market participation among mixed farmers for improving households’ income, ensuring food security, and improving livelihoods.